4. A Missing Link in Empowerment Program in Indonesia - I Wayan Suadnya (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2008)
Abstrak Pemerintah daerah telah diberikan otoritas untuk melaksanakan program pemberdayaan. Dukungan regulasi dan keuangan telah diberikan oleh pemerintah pusat dan badan pemberdayaan masyarakat juga telah di bentuk. Namun dampak dari program pemberdayaan masih rendah. Apa yang menyebabkan hal ini terjadi? Untuk menjawab pertanyaan ini survei dengan wawancara langsung dan wawancara mendalam dengan stakeholder kunci telah dilakukan di tujuh desa pesisir di Lombok. Hasil penelitian menunjukkan, walaupun berbagai upaya telah dilakukan oleh pemerintah untuk memberdayakan masyarakat pesisir, namun aparat pemerintah yang diharapkan melaksanakan program pemberdayaan tidak dilatih tentang pemberdayaan itu sendiri. Akibatnya aparat tidak mempunyai pengetahuan, keterampilan, dan prilaku yang memberdayakan sehingga mereka tetap mengimplementasikan cara lama yang top down dan pendekatan target. Hal ini berakibat pada gagalnya program. Abstract Local government was given authority to implement empowerment programs. Support including regulations, and financial were also provided by the central government. Empowerment bureau was established to accelerate empowerment programs. However, the impact of the empowerment program was low. What missing in government effort to empower coastal community in Lombok? To answer this question, a survey with face to face interview and in-depth interview with key stakeholders was carried out in seven coastal villages. The results indicate, even though various efforts have been carried out by the government to empower coastal communities, government staff who implement empowerment program were not trained on empowerment. As a result there was no change in government staff members’ knowledge, skills and behaviours, and staff continued practising the old top down mode of delivery and target focused approach to development processes. This had led to program failure.